Sistematización de los procesos de inspección de obras especiales desarrolladas en Recope - Álvarez-Herrera, Hellen (Instituto Tecnológico de Costa Rica, 2011)
Inspection is the process that is performed to verify that the desired quality is achieved in a given activity. There are many methods for implementing inspection processes in the field of construction project development, therefore the development of a classification is recommended only for each specific company, considering what type of works carried out more frequently and the type of staff that has to develop it. A manual inspection is one of the most common, along with checklists, but the construction companies in Costa Rica are applied infrequently, it is advisable to introduce these elements to improve controls and better buildings and projects. This project will design and develop these methods to Recope. The manual gives a brief explanation of the main processes to be followed in the field, and regulations and institutions involved in the construction processes and lists the most important elements to help oversee construction inspector, not to let important information forgotten or recorded.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2011.
Keywords: Normativa; Inspector de obra; Procesos constructivos; Inspección técnica; Análisis